A Conversation on Tamara Cohn Eskenazi's Ezra: A New Translation with Introduction and Commentary, Anchor Yale Bible 14A - Buster, Aubrey E.; Jones, E. Allen; Nash, Libbie; Fried, Lisbeth S.; Nam, Roger S.; Fulton, Deirdre N.; Williamson, H. G. M.; Eskenazi, Tamara Cohn (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2025)
This special collection contains revised essays from a 2023 SBL panel on Tamara Cohn Eskenazi’s Anchor Bible commentary on Ezra. Contributors assess her portrayal of Ezra’s political artistry and formation of “peoplehood,” engage major debates in Ezra–Nehemiah scholarship, and reflect on the role and limits of the commentator in reconstructing history and interpreting the text amid contemporary resonances.